Autopsy Cases of Convict Arrest and Custody Deaths in Trabzon Branch of the Council of Forensic Medicine Between Years of 1998-2007 - Birincioğlu, İsmail and Teke, Hacer Yaşar and Turan, Nurşen and Boz, Halil (The Bulletin of Legal Medicine, 2009)
Prisons and houses of arrest are under supervision of the government. Any death at these places must be investigated by thoroughly and detailed autopsy what should be conducted to exclude all possibilities of doubt. The aim of this study is to explore the reason, origin and demographic findings of prison deaths in Trabzon Branch of the Council of Forensic Medicine of Turkey and to make contribution to the national literature. The legal and medical reports of convict or arrest deaths in Trabzon Branch of the Council of Forensic Medicine of Turkey between years of 1998-2007 were investigated retrospectively. All data were evaluated statistically with SPSS 13.0 program. Test of chi-square was used in comparison for years. 0.05 was accepted as level of meaningfulness in statistical analysis. Totally 36 arrest and prison deaths were determined. 97.2% (n:35) of total cases were arrest and 2.8% (n:l) were probation, 97.2% of cases (n:35) were male, while only one case (2.8%) was woman. 69.4% (n:25) were natural and 27.8% (n:10) of deaths were unnatural. In only one case, tvpe of the death couldn’t be defined. 80% (n:8) of the unnatural deaths were suicide and 20% (n:2) were homicide. Data obtained were mainly in concordance with literature data. The reason of discordance was explored and discussed. Data about prison and arrest deaths in Turkey is important in order to take measures for the risk of these type of deaths. Autopsy in these cases is crucially important to exclude all possibilities of doubt. All convict or arrested people must have healthy environment and reach health services easily. They must be kept away from any media in which they can easily give harm themselves in. Key words: Prison, death, autopsy